Monetary policy in the presence of supply constraints: Evidence from German firm-level data - Almut Balleer; Marvin Noeller (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Using unique firm-level survey data from Germany, this paper investigates two measures of supply constraints: a new direct measure that indicates material shortages and capacity utilization, a widely accepted measure of bottlenecks and slack. We document substantial heterogeneity in supply constraints both across and particularly within industries and show that material constraints are not very persistent at the firm-level. We also show that high capacity utilization is not indicative of the presence of material constraints at the firm-level. We then ask how supply constraints propagate monetary policy shocks. We find that material-constrained firms increase prices substantially more often than unconstrained firms in response to expansionary monetary policy shocks, even when capacity utilization is low. Our results therefore suggest that material constraints exert substantial inflationary pressure in times of loose monetary policy. – – Anhand einzigartiger Erhebungsdaten deutscher Industrieunternehmen untersucht diese Studie zwei Maße für Angebotsengpässe: ein neues direktes Maß für Materialengpässe sowie Kapazitätsauslastungen in der Produktion. Wir dokumentieren eine beträchtliche Heterogenität in Angebotsengpässen sowohl zwischen als auch innerhalb von Branchen und zeigen, dass Materialengpässe auf Unternehmensebene nicht sehr dauerhaft sind. Wir zeigen auch, dass eine hohe Kapazitätsauslastung nicht notwendigerweise auf das Vorhandensein von Materialengpässen auf Unternehmensebene hindeutet. Anschließend gehen wir der Frage nach, wie Angebotsengpässe die Transmission geldpolitischer Schocks beeinflussen. Wir stellen fest, dass Unternehmen mit Materialengpässen ihre Preise als Reaktion auf expansive geldpolitische Schocks wesentlich häufiger erhöhen als Unternehmen ohne Materialengpässe, selbst wenn die Kapazitätsauslastung niedrig ist. Unsere Ergebnisse deuten daher darauf hin, dass materielle Beschränkungen in Zeiten einer lockeren Geldpolitik einen erheblichen Inflationsdruck ausüben.
Keywords: E31; E52; C22; 330; Supply constraints; capacity utilization; price setting; local projections; monetary policy